2022
DOI: 10.1002/14651858.cd012558.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Clinical judgement by primary care physicians for the diagnosis of all-cause dementia or cognitive impairment in symptomatic people

Abstract: Clinical judgement by primary care physicians for the diagnosis of all-cause dementia or cognitive impairment in symptomatic people. Cochrane Database of Systematic Reviews, 2017(2), [CD012558].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 144 publications
1
8
0
Order By: Relevance
“…47 In the context of primary care, meta-analyses found that general practitioners achieved an F1-score of 0.735 when screening for dementia and an F1-score of 0.785 when screening for cognitive impairment. 2 Our pipeline, using only primary care-accessible features (tier 1), outperformed these findings, with an AD dementia screening F1-score of 0.919 and a cog-nitive impairment screening F1-score of 0.889. These results were robust across classification methodology.…”
Section: Discussionmentioning
confidence: 71%
“…47 In the context of primary care, meta-analyses found that general practitioners achieved an F1-score of 0.735 when screening for dementia and an F1-score of 0.785 when screening for cognitive impairment. 2 Our pipeline, using only primary care-accessible features (tier 1), outperformed these findings, with an AD dementia screening F1-score of 0.919 and a cog-nitive impairment screening F1-score of 0.889. These results were robust across classification methodology.…”
Section: Discussionmentioning
confidence: 71%
“…This month's Cochrane Review (Creavin 2022) aimed to assess the clinical accuracy of GPs in diagnosing two target conditions: dementia and mild cognitive impairment. This article will focus on the primary outcome analysed, namely, the clinical accuracy of GPs in diagnosing dementia, as defined by sensitivity and specificity (Box 2).…”
Section: The Cochrane Reviewmentioning
confidence: 99%
“…For instance, there may be delays in seeking help due to poor recognition and understanding of symptoms as well as a reluctance to seek help because of stigma (National Collaborating Centre for Mental Health 2018). Primary care services are often the first point of contact for people with dementia and therefore form an important interface in determining which patients require referral to specialist services for further assessment (Pentzek 2019; Creavin 2022). In fact, previous studies have found that a general practitioner's (GP's) clinical judgement is a known added predictor for identification of individuals at risk of dementia (Box 1) (Pentzek 2019).…”
mentioning
confidence: 99%
“…Alzheimer's Disease International estimate that, on average, > 75% of people living with cognitive complaints or impairment are undiagnosed worldwide 3 and post mortem studies report misdiagnosis rates of up to 30% 4 . Furthermore, a meta‐analysis reported that the clinical judgment of general practitioners had a sensitivity of 58% and a specificity of 89% in the diagnosis of dementia, meaning that false negative diagnoses are likely 5 …”
Section: Introductionmentioning
confidence: 99%
“…4 Furthermore, a meta-analysis reported that the clinical judgment of general practitioners had a sensitivity of 58% and a specificity of 89% in the diagnosis of dementia, meaning that false negative diagnoses are likely. 5 Globally, there is no standardized AD diagnostic pathway. 6 At present, symptomatic individuals with clinical suspicion of AD undergo a combination of clinical history taking, cognitive assessments, routine laboratory tests (e.g., blood and/or urine tests), and structural brain imaging (e.g., computed tomography or magnetic resonance imaging…”
Section: Introductionmentioning
confidence: 99%